Analisis Pengaruh Kepercayaan Konsumen, Persepsi Manfaat Dan Persepsi Kemudahan Penggunaan Terhadap Minat Beli Pada Media Sosial Instagram (Studi Kasus Pada Online Shop “Rp” Shop Kota Metro) - Fitriani; Bambang Suhada; Lilis Asmara (Jurnal Manajemen DIVERSIFIKASI, 2025)
This research aims to find out whether Consumer Trust, Perception of Benefits andPerception of Ease of Use influence Purchase Intention. A quantitative approach was used inthis research, namely an approach where the data is in the form of numbers or qualitativefigures. The population in this study were active Instagram followers of Rpshop Metro City.Taking the minimum number of research samples is by multiplying the indicators by thenumbers 5 to 10, then the indicators in the existing variables are 16 multiplied by the number5, which is 80 respondents. The data collection technique used was using interviews,documentation and questionnaires. Data analysis used includes validity test, reliability test,normality test, linearity test, homogeneity test and multiple linear regression analysis withthe help of the SPSS version 25.0 application. Consumer Trust, Perception of Benefits andPerception of Ease of Use have a positive and significant influence on Purchase Interest atRp Shop Kota Metro